Coverage, field specialisation and the impact of scientific publishers indexed in the Book Citation Index. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The aim of this study is to analyse the disciplinary coverage of Thomson Reuters' Book Citation Index database focusing on publisher presence, impact and specialisation.Design/methodology/approach – The authors conducted a descriptive study in which they examined coverage by discipline, publisher distribution by field and country of publication, and publisher impact. For this purpose the Thomson Reuters' subject categories were aggregated into 15 disciplines.Findings – Humanities and social sciences comprise 30 per cent of the total share of this database. Most of the disciplines are covered by very few publishers mainly from the UK and USA (75.05 per cent of the books), in fact 33 publishers hold 90 per cent of the whole share. Regarding publisher impact, 80.5 per cent of the books and chapters remained uncited. Two serious errors were found in this database: the Book Citation Index does not retrieve all citations for books and chapters; and book citations do not include citations to their chapters.Originality/value – There are currently no studies analysing in depth the coverage of this novel database which covers monographs. Acknowledgements : Thanks are due to the three anonymous referees for their constructive suggestions. Thanks are also due to Bryan J. Robinson Fryer for reviewing the English version of this paper. This research was sponsored by the Spanish Ministry of Economy and Finance under grant HAR2011‐30383‐C02‐02. Nicolás Robinson‐García is currently supported by an FPU grant from the Ministry of Economy and Finance.